2018
DOI: 10.1088/1755-1315/105/1/012030
|View full text |Cite
|
Sign up to set email alerts
|

Effect of graphenenano-fluid on heat pipe thermal performance for passive heat removal in nuclear spent fuel storage pool

Abstract: Abstract. After Fukushima Dai-ichi nuclear power reactor accident, spent fuel in spent fuel storage pool (SFSP) became an important thing to pay attention to, due to its decay heat release. If station blackout occurred, the active system for SFSP cooling system will experience malfunction to remove the product of decay heat. To keep spent fuel safe, heat pipe as passive cooling system device can be used to remove spent fuel decay heat even if the active cooling system failed. Heat pipe with 6 m on length will … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
2
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 14 publications
1
2
0
Order By: Relevance
“…In overall, the use of nanographene improves the thermal performance of the heat pipe. This investigation results are in agreement with the results obtained by other researchers [28,30,34]. The thermal resistance of vertical straight wickless-heat pipe using Graphene nanofluid obtained was compared with other researchers result.…”
Section: Thermal Resistancesupporting
confidence: 92%
See 2 more Smart Citations
“…In overall, the use of nanographene improves the thermal performance of the heat pipe. This investigation results are in agreement with the results obtained by other researchers [28,30,34]. The thermal resistance of vertical straight wickless-heat pipe using Graphene nanofluid obtained was compared with other researchers result.…”
Section: Thermal Resistancesupporting
confidence: 92%
“…The preliminary investigation was only focused on the effect of heat load given to the heat pipe evaporator with 1 % Graphene nanofluid weight concentration. Our preliminary result showed that the use of Graphene nanofluid could enhance the thermal performance of the heat pipe to transfer heat from the heat source to the heat sink [34].…”
Section: Introduction mentioning
confidence: 90%
See 1 more Smart Citation